PENGARUH KARAKTERISTIK MEREK, KARAKTERISTIK PERUSAHAAN, KARAKTERISTIK PELANGGAN TERHADAP LOYALITAS PELANGGAN OTSKY DI BANDAR LAMPUNG - Gandasurya, Dilan Darizki; Bakti, Dadang Karya; Harori, M. Iqbal (Jurnal Kompetitif Bisnis, 2023)
This study aims to determine the influence of brand characteristics, company characteristics, customer characteristics on the brand loyalty of Otsky in Bandar Lampung. This type of quantitative research with a descriptive approach. The population in this study were customers of the Otsky store in Bandar Lampung. The sampling technique used purposive sampling with a sample of 100 respondents. The data were obtained from questionnaires using a Likert scale. The data analysis method used in this research is quantitative analysis which includes: validity test, reliability test, and multiple linear regression, and the research hypothesis is tested using the individual parameter significance test (T test), simultaneous significance test (F test), and determination. coefficient analysis (). The results showed that simultaneously three independent variables, namely brand characteristics (X1), company characteristics (X2), customer characteristics (X3) had a positive and significant effect on customer loyalty (Y) Otsky Store in Bandar Lampung. The partial test also shows that all of the respective variables have a positive effect on customer loyalty at Otsky Store in Bandar Lampung.